BEYOND VOCABULARY SIZE: WORD CLASS MASTERY AND WRITING SKILLS IN EFL STUDENTS - Kaniadewi, Nita; Septi Diana, Safira (ELLTER Journal, 2026)
This study examines the correlation between word class mastery and students’ writing skills, addressing the limited attention given to specific grammatical dimensions of vocabulary in writing research. A quantitative correlational design was employed, involving 35 third-semester students of the English Language Education program at the University of Muhammadiyah Prof. Dr. Hamka. Data were collected through a word class test and a writing test and analyzed using Microsoft Excel and SPSS. The results reveal a very strong and statistically significant positive correlation between word class mastery and students’ writing skills (r = 0.987, p < 0.01, two-tailed). This finding suggests that students with higher mastery of word classes tend to demonstrate better writing performance. However, the exceptionally high correlation should be interpreted with caution, as it may reflect overlapping constructs, the relatively small and homogeneous sample, and similarities in the assessment design. This study contributes to the literature by highlighting word class mastery as a specific and functionally important component of vocabulary knowledge in writing. Pedagogically, the findings suggest the need to integrate explicit grammar instruction into writing activities. Further research with larger and more diverse samples is recommended to validate these findings.